Transdiagnostic versus disorder-specific and clinician-guided versus self-guided internet-delivered treatment for Social Anxiety Disorder and comorbid disorders: A randomized controlled trial. (August 2016) - Dear, B.F.; Staples, L.G.; Terides, M.D.; Fogliati, V.J.; Sheehan, J.; Johnston, L.; Kayrouz, R.; Dear, R.; McEvoy, P.M.; Titov, N.
Highlights: Study compared disorder-specific and transdiagnostic treatment approaches. Study also compared clinician-guided and self-guided treatment approaches. Study is 1 of 4 related randomized controlled trials examining these issues. Study focused on Social Anxiety Disorder and comorbid disorders. No marked differences were observed between the treatment approaches. Abstract: Disorder-specific (DS-CBT) and transdiagnostic (TD-CBT) cognitive behaviour therapy have both been used to treat social anxiety disorder (SAD). This study compared internet-delivered DS-CBT and TD-CBT for SAD across clinician-guided (CG-CBT) and self-guided (SG-CBT) formats. Participants with SAD (n = 233) were randomly allocated to receive internet-delivered TD-CBT or DS-CBT and CG-CBT or SG-CBT. Large reductions in symptoms of SAD (Cohen's d ≥ 1.01; avg. reduction ≥ 30%) and moderate-to-large reductions in symptoms of comorbid depression (Cohen's d ≥ 1.25; avg. reduction ≥ 39%), generalised anxiety disorder (Cohen's d ≥ 0.86; avg. reduction ≥ 36%) and panic disorder (Cohen's d ≥ 0.53; avg. reduction ≥ 25%) were found immediately post-treatment and were maintained or further improved to 24-month follow-up. No marked differences were observed between TD-CBT and DS-CBT or CG-CBT and SG-CBT highlighting the potential of each for the treatment of SAD and comorbid disorders.